Body image, self-esteem, and quality of life in patients with psoriasis - Hulya Nazik; Selcuk Nazik; Feride C Gul (Wolters Kluwer Medknow Publications, 2017)
Background: Psoriasis is a chronic inflammatory disease of the skin that may affect the visible areas of body. Hence, the quality of life, self-esteem, and body image can be affected in psoriasis patients. Objectives: We aimed in the present study to assess the effects of psoriasis on the quality of life, self-esteem, and body image. Materials and Methods: The study included 92 patients with psoriasis, along with 98 control participants. The sociodemographic characteristics of the patients were assessed, their Psoriasis Area Severity Index (PASI) scores were calculated to determine the clinical severity of the psoriasis, and the values were recorded. In addition, Dermatology Life Quality Index (DLQI), Body Image Scale, and Rosenberg Self-Esteem Scale results were evaluated. Results: When the control and psoriasis groups were evaluated regarding the DLQI, self-esteem, and body image, quality of life was found to be more negatively affected in the psoriasis group than the controls, which was statistically significant (P < 0.001), and self-esteem (P < 0.001) and body image (P < 0.001) were found to be significantly lower. Educational status significantly affected self-esteem (P < 0.001) and body image (P = 0.021), however, quality of life was not significantly affected by this parameter (P = 0.345). PASI was positively correlated with the quality of life (r = 0.703) and self-esteem (r = 0.448), however, it was negatively correlated with the body image (r = −0.423). Conclusions: Psoriasis may negatively affect quality of life, self-esteem, and body image, and may also cause psychosocial problems. An assessment of new approaches on this issue may contribute to developments in the treatment of and rehabilitation from this disease.